Szkolnictwo zawodowe w Częstochowie w latach 1945–1989. Zarys problematyki - Wrona, Izabela (Poznańskie Towarzystwo Przyjaciół Nauk we współpracy z Zakładem Historii Wychowania, WSE UAM, 2012)
The process of making the educational system public and its democratization after the Second World War was reflected, to a large extent, in the vocational education. The development of this kind of education became possible after the state had taken over the basic branches of economy, which had an influence upon easier access to different types and levels of employment. This complex process rendered the social advancement of the working class possible. The beginnings of this professional advancement date back not only to the years of the Second World War but also to the period between the First World War and the Second World War when Janusz Jędrzejewicz passed a bill which changed the attitude towards the vocational education. The social and cultural development of the broad masses removed the obstacles standing in the way to the higher levels of education by making many procedures accessible, among others: free education, development of the system of scholarships and boarding schools, removing blind alleys in the educational system and, first of all, creating a complex system of schools for the working people. The school system which was implemented at that time was treated as an example during the first years after the Second World War.
Vocational Education in Częstochowa Between 1945–1989. The Outline of the Problem.
Keywords: Vocational Education; Częstochowa